2008
DOI: 10.1111/j.1939-165x.2008.00085.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative clinical study of canine and feline total blood cell count results with seven in‐clinic and two commercial laboratory hematology analyzers

Abstract: Background-A CBC is an integral part of the assessment of health and disease in companion animals. While in the past newer technologies for CBC analysis were limited to large clinical pathology laboratories, several smaller and affordable automated hematology analyzers have been developed for in-clinic use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
81
2
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(93 citation statements)
references
References 17 publications
(30 reference statements)
6
81
2
4
Order By: Relevance
“…In previous studies comparing impedance and flow cytometrybased platelet counts in cats, both comparatively higher and lower impedance-based counts have been reported. 2,5,24 Correlations for baseline and postagonist platelet counts between the 2 analyzers ranged from 0.70 to 0.77 (Table 2), likely reflecting some imprecision of platelet counts by both analyzers. A limitation of our study is that only 1 value with the flow cytometry-based analyzer was obtained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies comparing impedance and flow cytometrybased platelet counts in cats, both comparatively higher and lower impedance-based counts have been reported. 2,5,24 Correlations for baseline and postagonist platelet counts between the 2 analyzers ranged from 0.70 to 0.77 (Table 2), likely reflecting some imprecision of platelet counts by both analyzers. A limitation of our study is that only 1 value with the flow cytometry-based analyzer was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…The mean (range) baseline platelet counts by flow cytometry in our study were similar to previous studies on a similar analyzer, which reported a mean of 281 × 10 9 /liter, with 2.5th and 97.5th percentile of 42 and 630 × 10 9 /liter, respectively, and a mean (range) of 289 (16-858) × 10 9 /liter, using EDTAanticoagulated blood. 5,30 The RI provided by the manufacturer of the impedance analyzer is 300-800 × 10 9 /liter. In previous studies comparing impedance and flow cytometrybased platelet counts in cats, both comparatively higher and lower impedance-based counts have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Dewhurst et al (2003), observaram excelente correlacao do VG determinado por impedância utilizando dois aparelhos comerciais em amostras de cães e gatos. Becker et al (2008), comparando aparelhos eletrônicos com diferentes tecnologias, obtiveram uma excelente correlação entre os metodos em amostras de cães e gatos.…”
Section: Discussionunclassified
“…The manual counts are affected by human counting errors (Becker et al, 2008). Thus, comparing the ACI results with the MC might bring more uncertainty to the comparison process.…”
Section: Discussionmentioning
confidence: 99%
“…This is mainly due to the variety of animal species and the difficulty in finding an economically viable technical approach capable of handling all variations (e.g., concentration, size and shape) in those blood samples. Additionally, the tests carried out in electrical impedance based equipments require the use of specific reagents for each animal species (Becker et al, 2008). This feature leads to the lack of reagent for some species and the need for the laboratory to have many reagents even when few tests are needed for a given species.…”
Section: Introductionmentioning
confidence: 99%